GC-MS Characterization and Physicochemical Profiling of Saplint Plus: A Potent Anti-Inflammatory Liniment (AYUSHDHARA, 2025)
Aches and pains significantly impact an individual's quality of life, often arising from natural aging, chronic conditions like degenerative arthritis, or fibromyalgia. This study aims to characterize the physicochemical properties and chemical composition of Saplint Plus, a potential anti-inflammatory liniment, using advanced analytical techniques. Physicochemical evaluations, including, viscosity, density, solubility, and thermal stability, were conducted to assess its suitability for topical application. Gas chromatography-mass spectrometry (GC-MS) were employed to identify and profile the bioactive phytochemical constituents. The results revealed that Saplint Plus exhibits optimal physicochemical properties, such as ideal pH, viscosity, and stability, for topical use. GC-MS analysis identified 21 bioactive compounds, with cyclohexanol, thymol, and eucalyptol as major constituents, which are known for their anti-inflammatory properties. These findings highlight the robust chemical composition of Saplint Plus, underscoring its potential as a therapeutic liniment. The study concludes that Saplint Plus possesses promising physicochemical characteristics, making it a viable candidate for anti-inflammatory applications. Further research is recommended to explore its therapeutic efficacy and optimize its formulation.